2021
DOI: 10.1097/gox.0000000000003668
|View full text |Cite
|
Sign up to set email alerts
|

Best Clinical Practices with ATX-101 for Submental Fat Reduction: Patient-related Factors and Physician Considerations

Abstract: Background: Submental fat can be reduced with ATX-101 (deoxycholic acid injection), a customizable and minimally invasive alternative to liposuction. In the years since its approval, the treatment patterns of ATX-101 have evolved. Methods: A panel of experienced physicians from the United States gathered to generate best practices for the use of ATX-101 in submental contouring. Results: The expert panel provided their insights on appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Over 90% of patients treated with ATX-101 in open-label clinical trials or the REFINE trial showed either improvement or no change in the submental fullness. However, patients with excess sub-platysmal fat or severe submental skin laxity may be better treated by alternative treatment options to address submental fullness or skin-tightening therapy along with ATX-101 administration [22,23]. Teller et al [23] reported in their study that for the reduction of SMF, the finest clinical practices regarding the use of ATX-101 should enable physicians to boost treatment outcomes and patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of patients treated with ATX-101 in open-label clinical trials or the REFINE trial showed either improvement or no change in the submental fullness. However, patients with excess sub-platysmal fat or severe submental skin laxity may be better treated by alternative treatment options to address submental fullness or skin-tightening therapy along with ATX-101 administration [22,23]. Teller et al [23] reported in their study that for the reduction of SMF, the finest clinical practices regarding the use of ATX-101 should enable physicians to boost treatment outcomes and patient experience.…”
Section: Discussionmentioning
confidence: 99%
“…However, they may necessitate multiple sessions, and the results can take time to become noticeable. On the other hand, non-surgical energy-based methods, such as radiofrequency devices and cryolipolysis, can provide more rapid results with a single session but may entail discomfort during treatment and potentially longer recovery times due to swelling and bruising [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing concern regarding these issues has driven interest in non-invasive and minimally invasive treatments for submental fat and tissue laxity. Patients now have various treatment options, including injectable treatments, nonsurgical energy-based methods, and surgical procedures [1][2][3][4][5][6][7][8][9][10]. One minimally invasive option is laser lipolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of a laser source, which primarily makes up laser lipolysis devices, 12 can be upward of $1500. 13 In addition, deoxycholic acid, 14 as a nonregulated commercial product, can cost almost $500 for 100 mg of product. 15 To overcome such limitations, we have investigated a potential new, low-cost, nonsurgical fat reduction modality involving the use of in situ water hydrolysis to modify the biochemical and physical tissue properties.…”
mentioning
confidence: 99%